D-Lib magazine (Corp. for National Research Initiatives, 1995)
Presents "D-Lib Magazine," a monthly electronic publication related to digital libraries. Includes commentaries and news articles. Offers an archive of back issues and a site search engine. Provides access to working groups, digital library research projects, events calendars, and related technical reports. Notes access terms and conditions and links to mirror sites. Links to the Corporation for National Research Initiatives, the coordinator of the magazine.